2018
DOI: 10.1039/c8ta05157g
|View full text |Cite
|
Sign up to set email alerts
|

A homogeneous grain-controlled ScSZ functional layer for high performance low-temperature solid oxide fuel cells

Abstract: Scandia-stabilized zirconia (ScSZ) is employed as a cathodic functional layer onto yttria-stabilized zirconia based fuel cell systems for low-temperature solid oxide fuel cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…Although the total thickness of the electrolyte increases due to insertion of the ALD GDC functional layer, there is no significant difference in the size of the first semi-circle. 22 This result is due to both the relatively small (~50 nm) thickness increment resulting from addition of ALD GDC compared to total YSZ thickness as shown in Figure 9A-B and the relatively high ionic conductivity of doped-ceria materials (over an order of magnitude higher) compared to YSZ. 1,7 Thus, there was a negligible increase of ionic transport resistance and a significant decrease of electrode/electrolyte interface resistance when the ALD GDC functional layer was applied.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Although the total thickness of the electrolyte increases due to insertion of the ALD GDC functional layer, there is no significant difference in the size of the first semi-circle. 22 This result is due to both the relatively small (~50 nm) thickness increment resulting from addition of ALD GDC compared to total YSZ thickness as shown in Figure 9A-B and the relatively high ionic conductivity of doped-ceria materials (over an order of magnitude higher) compared to YSZ. 1,7 Thus, there was a negligible increase of ionic transport resistance and a significant decrease of electrode/electrolyte interface resistance when the ALD GDC functional layer was applied.…”
Section: Resultsmentioning
confidence: 95%
“…Figure 10B shows a significant decrease of electrode/electrolyte interface resistance in the sample using ALD GDC, while the ionic transport resistance was essentially unchanged. Although the total thickness of the electrolyte increases due to insertion of the ALD GDC functional layer, there is no significant difference in the size of the first semi‐circle 22 . This result is due to both the relatively small (~50 nm) thickness increment resulting from addition of ALD GDC compared to total YSZ thickness as shown in Figure 9A‐B and the relatively high ionic conductivity of doped‐ceria materials (over an order of magnitude higher) compared to YSZ 1,7 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, this was not beneficial for suppressing defects such as pinholes, which were generated on the porous supporting structure. Some studies recently demonstrated that the columnar grain growth of thin-film electrolyte with sputtering can be reduced, resulting in sufficiently dense, pinhole-free films even when deposited on porous AAO substrates. ,,, …”
Section: Introductionmentioning
confidence: 99%
“…In addition, the activation energies of doped-ceria materials (<0.8 eV) were less than zirconia-based systems (>1.0 eV). , ,,, Therefore, doped-ceria systems are usually adopted as a cathode functional layer located between the cathode and electrolyte to facilitate the ORR. Most studies successfully demonstrated enhanced ORR kinetics resulting in high performance TF-SOFCs, but they only focused on the high ionic conductivity of the material. Some recent works showed that the surface grain boundary density of thin-film electrolytes is strongly related to the surface oxygen incorporation rate. ,,,, Specifically, they showed that the grain boundary has more oxygen vacancies than the grain interior due to intrinsic material property and the segregation of dopant, which helps oxygen ion incorporation.…”
Section: Introductionmentioning
confidence: 99%